A Processability Theory Study: Past -ed Acquisition in University Learners in Indonesia - Ima Widyastuti (Universitas Ahmad Dahlan, 2015)
Abstract This study is to see the Past –ed morphological acquisition which is placed on the Stage 2 of the Processability Theory (PT). The participants of this study were 26 university students in speaking classroom at Sarjanawiyata Tamansiswa University, Indonesia. The data, which was gathered from semi-structure individual interviews with several topics, were analysed using an Emergence Criterion (Pienemann, 1998). The present study found that all participants did not acquire the Past -edon Stage 2 of English Developmental Stages. Several possible reasons were discussed in the study to find out why they were not able to produce Past –ed forms. However, the further research is also required due to the very limited research on this case.